2016
DOI: 10.1177/0887403415573774
|View full text |Cite
|
Sign up to set email alerts
|

An Outcome Evaluation of the Indianapolis Community Court

Abstract: Seeking to alleviate traditional criminal justice system processing for low-level non-violent crimes, community courts have emerged as a viable alternative. These courts use innovative community-based efforts to address the needs of defendants charged with quality-of-life crimes and attempt to improve the surrounding community. Using a retrospective quasi-experimental design, this research examines recidivism outcomes for a sample of 574 defendants who were referred to the Indianapolis Community Court. Repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…An evaluation study of the East of the River CC program in Washington State found a 42 percent reduced risk of program graduates being reconvicted (Westat 2012). By contrast, some studies have found no significant effect (Sviridoff et al 2002;Jolliffe and Farrington 2009;Booth et al 2012;Grommon, Hipple, and Ray 2017). Focusing on costefficiency, the RHCJC evaluation study estimated that, based on reduced victimization costs owing to reductions in recidivism, the benefits of processing cases in the RHCJC's CC outweighed its total cost by nearly two to one (Lee et al 2013).…”
Section: Evaluating the Effectiveness Of Community Courtsmentioning
confidence: 99%
“…An evaluation study of the East of the River CC program in Washington State found a 42 percent reduced risk of program graduates being reconvicted (Westat 2012). By contrast, some studies have found no significant effect (Sviridoff et al 2002;Jolliffe and Farrington 2009;Booth et al 2012;Grommon, Hipple, and Ray 2017). Focusing on costefficiency, the RHCJC evaluation study estimated that, based on reduced victimization costs owing to reductions in recidivism, the benefits of processing cases in the RHCJC's CC outweighed its total cost by nearly two to one (Lee et al 2013).…”
Section: Evaluating the Effectiveness Of Community Courtsmentioning
confidence: 99%
“…In contrast, three studies found no significant reductions in reoffending, two focusing on the North Liverpool Community Justice Centre in England (Booth et al 2012; Jolliffe and Farrington 2009) and one on defendants referred to the Indianapolis Community Court (Grommon, Hipple, and Ray 2017).…”
Section: Introductionmentioning
confidence: 97%